THE EXPRESSIONS OF CORRECTIVE FEEDBACK IN SECOND LANGUAGE CLASSROOM - Sulistyani Sulistyani (Universitas PGRI Madiun, 2014)
This study aims to review the teacher’s expressions which constitute teacher’s corrective feedbacks (CFs) in oral production and examine the ways the teachers' expression revealing teacher’s CFs. The data are in the forms of teachers' utterances obtained from four research articles. The result shows that teacher' expressions which constitute CFs cover explicit correction, recast, clarification request, metalinguistic, elicitation, and repetition. While the ways which reveal teacher’s CFs are found to be reduction, negation, and expansion. The area to be corrected commonly involves phonological, grammatical, and lexical errors. So, it can be concluded that in a second language classroom instruction, teacher’s CFs expressions lead learners' erroneous utterances to be resolved because by saying